Rancang Bangun Aplikasi E-Commerce Ukm Kota Pari Berbasis Woocommerce - Muttaqin, Muhammad (CV. Hawari, 2022)
Marketing trends are shifting from conventional (offline) to digital (online). E-Commerce applications for business actors can market their products from anywhere and anytime via the internet. The focus of the issues raised are: (1) How to Design Woocommerce-Based E-Commerce Applications (2) How to Implement E-Commerce Applications for Small and Medium Enterprises (SMEs) in Kota Pari Village. To reveal these problems, this study uses qualitative research that is useful for providing facts and data regarding the Design of Woocommerce-Based E-Commerce Applications for Small and Medium Enterprises (SMEs) in Kota Pari Village, then the data is analyzed using a grounded method with a theoretical approach that provides development to field of research study. Then the data collection techniques used interview, documentation, and observation techniques. Data analysis techniques with data reduction, data presentation and drawing conclusions. While the theory used in this research is an integrated marketing trend communication theory combined with Woocommerce techniques. From the results of the study it was found that through the E-Commerce Application, business actors can establish relationships with customers in a fast response. The benefits of implementing an E-Commerce Application are related to the 4P marketing trends (product, price, place and promotion). Suggestions for SMEs in Kota Pari Village must continue to update marketing trends, both conventional and digital, consistently, especially regarding E-Commerce applications, they can be developed again in their management, because so far they are still managed by each business actor.